A Hierarchical Spatial Fuzzy C Means Algorithm for Mammographic Mass Segmentation - Hazarika, Manasi; Mahanta, Lipi B (International Journal of Computer Sciences and Engineering, 2019)
Fuzzy C Means is one of the most popular machine learning technique for image segmentation. However, traditional Fuzzy C Means is insensitive to noise as it does not consider spatial information. To solve this issue a wide variety of modified Fuzzy C means techniques, considering spatial information of pixels, are proposed by different researchers. In this paper we propose a hierarchical Fuzzy C Means algorithm considering spatial features of image pixels. Our method aims to overcome the shortcomings of traditional Fuzzy C Means by incorporating spatial feature as well as the issue of misclassification of pixels associated with single level clustering. The proposed method divides the original image pixels into a set of clusters using a spatial fuzzy C means technique in the first level of the hierarchical model. In the second level of the hierarchy, the cluster which contains the candidate mass is further divided into sub clusters using traditional Fuzzy C Means algorithm to yield the final segmentation result. The experimental outputs show improved segmentation result by our proposed method.